Digital Literacy and Technological Resources on MSME Performance Through Their Adaptation - Ismail Saleh; Umi Mu’awanah; Djuni Farhan; Fx. Bhakti Hendrakusuma (Pusat Publikasi Nusantara, 2025)
This study aims to test and analyze: 1) the influence of digital literacy on MSME adaptation, 2) the influence of technology resources on MSME adaptation, 3) the influence of digital literacy on MSME performance, 4) the influence of technology resources on MSME performance, 5) the influence of MSME adaptation on MSME performance, 6) the influence of digital literacy on MSME performance through MSME adaptation, 7) the influence of technology resources on MSME performance through MSME adaptation. This research was conducted in Mojokerto Regency in 2024, with a sample of 125 MSMEs. Data related to research variables were collected with a google form, then analyzed using Smart PLS software. The results prove that: 1) digital literacy has a significant positive effect on MSME adaptation, 2) technological resources have a significant positive effect on MSME adaptation, 3) digital literacy has a significant positive effect on MSME performance, 4) technological resources have a significant positive effect on MSME performance, 5) MSME adaptation has a significant positive effect on MSME performance, 6) digital literacy has a significant positive effect on MSME performance through adaptation MSMEs, 7) technological resources have a significant positive effect on the performance of MSMEs through MSME adaptation.